The Role of Employee Digital Literacy in Combating Mass Layoff Hoaxes on Social Media Platforms - Maddi, Jaenal Hasyim; Purnomo, Marlinda Irwanti (The Eastasouth Journal of Social Science and Humanities, 2025)
The advancement of digital technology has accelerated the flow of information widely and rapidly, but it also presents challenges in the form of hoaxes that can harm individuals and organizations. In the corporate context, mass layoffs (PHK) often become targets of fake news, causing panic and instability in the workplace. Employees play a crucial role in countering these hoaxes through strong digital literacy. This article examines how employees' digital literacy can contribute to combating mass layoff hoaxes on social media to maintain corporate stability. Using Katherine Miller’s organizational communication theory and the concept of digital literacy, this study highlights the importance of education and digital awareness in the workplace.